Utility of whole genome sequencing in assessing risk and clinically relevant outcomes for pulmonary fibrosis. Issue 6 (22nd December 2022) - Zhang, David; Newton, Chad A.; Wang, Binhan; Povysil, Gundula; Noth, Imre; Martinez, Fernando J.; Raghu, Ganesh; Goldstein, David; Garcia, Christine Kim
Background: Whole genome sequencing (WGS) can detect variants and estimate telomere length. The clinical utility of WGS in estimating risk, progression and survival of pulmonary fibrosis patients is unknown. Methods: In this observational cohort study, we performed WGS on 949 patients with idiopathic pulmonary fibrosis or familial pulmonary fibrosis to determine rare and common variant genotypes, estimate telomere length and assess the association of genomic factors with clinical outcomes. Results: WGS estimates of telomere length correlated with quantitative PCR (R=0.65) and Southern blot (R=0.71) measurements. Rare deleterious qualifying variants were found in 14% of the total cohort, with a five-fold increase in those with a family history of disease versus those without (25% versus 5%). Most rare qualifying variants (85%) were found in telomere-related genes and were associated with shorter telomere lengths. Rare qualifying variants had a greater effect on telomere length than a polygenic risk score calculated using 20 common variants previously associated with telomere length. The common variant polygenic risk score predicted telomere length only in sporadic disease. Reduced transplant-free survival was associated with rare qualifying variants, shorter quantitative PCR-measured telomere lengths and absence of the MUC5B promoter (rs35705950) single nucleotide polymorphism, but not with WGS-estimated telomere length or the common variant polygenic risk score. Disease progression was associated with both measures of telomere length (quantitative PCR measured and WGS estimated), rare qualifying variants and the common variant polygenic risk score. Conclusion: As a single test, WGS can inform pulmonary fibrosis genetic-mediated risk, evaluate the functional effect of telomere-related variants by estimating telomere length, and prognosticate clinically relevant disease outcomes. Whole genome sequencing yields rare and common variant genotypes and telomere length estimation to characterise disease risk and provide prognostic information regarding survival and progression for pulmonary fibrosis patients. https://bit.ly/3A8uVBe